2007
DOI: 10.1177/1077559507301842
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and Violent Delinquency: Disentangling Main Effects and Subgroup Effects

Abstract: This study employs data from the Chicago Longitudinal Study (CLS) to investigate the relation between child maltreatment and the incidence and frequency of violent delinquency. The authors also examine if effects vary between physically abused and neglected children and if select indicators (sex, cumulative risk, public aid receipt) moderate the connections between maltreatment and violent outcomes. The CLS follows a cohort of 1,539 low-income, minority children who attended public kindergarten programs in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(127 citation statements)
references
References 43 publications
7
113
2
2
Order By: Relevance
“…Most previ ous literature does not measure number of maltreatment types, just whether maltreatment occurred and, sometimes, which type (Smith and Thornberry, 1995;Maxfield and Widom, 1996;Lemmon, 1999;Wiebush et al, 2000;Mersky and Reynolds, 2007). More recently, however, it was found that experiencing multiple forms of maltreatment increased delinquency outcomes (Currie and Tekin, 2006) and that number of maltreatment types were linked to youth adju dication for a violent offense or multiple violent petitions (Mersky and Reynolds, 2007). Important additional information is needed to make sense of these con tradictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previ ous literature does not measure number of maltreatment types, just whether maltreatment occurred and, sometimes, which type (Smith and Thornberry, 1995;Maxfield and Widom, 1996;Lemmon, 1999;Wiebush et al, 2000;Mersky and Reynolds, 2007). More recently, however, it was found that experiencing multiple forms of maltreatment increased delinquency outcomes (Currie and Tekin, 2006) and that number of maltreatment types were linked to youth adju dication for a violent offense or multiple violent petitions (Mersky and Reynolds, 2007). Important additional information is needed to make sense of these con tradictions.…”
Section: Discussionmentioning
confidence: 99%
“…A history of maltreatment has been shown to be signifi cant even in the presence of these other risk factors (Smith and Thornberry, 1995;Maxfield and Widom, 1996;Lemmon, 1999;Wiebush et al, 2000), although most studies have documented a general link, and studies investigating an asso ciation between types of maltreatment individually (physical abuse, sexual abuse and neglect) and delinquency have been limited (Currie and Tekin, 2006;Mersky and Reynolds, 2007). That this would be worth doing is suggested by the findings of Widom and Maxfield (2001), Egeland et al (2002) and Fagan (2005), which showed that physical abuse and neglect victims have an elevated risk for later delinquency, but victims of sexual abuse do not.…”
Section: Maltreatment To Delinquency Linkmentioning
confidence: 99%
“…Several studies have supported the link between increased risk of aggression and juvenile delinquency in victims of abuse and neglect (e.g., Hawkins et al, 1998;Lemmon, 2006;Mersky & Reynolds, 2007; Stouthamer- Loeber, Wei et al, 2002). For example, Lemmon (2006) found that maltreatment recurrence was a significant factor in explaining initiation, continuation, and severity of delinquency, even when statistically controlling for other factors such as social class, geographic location, and race.…”
Section: Child Maltreatment and Dependencymentioning
confidence: 99%
“…9 Similarly, a culture of family violence contributes to making a community less safe. However, when children grow up in safe, [16][17][18] stable, 19 and nurturing relationships and environments, they learn empathy, impulse control, anger management, and problem-solving -all skills that protect against interpersonal, self-directed, and collective violence 20 and allow for learning, play, and healthy development. 21,22 Therefore, violence prevention helps generate viable ecologies that lead to economic growth and general well-being.…”
Section: Themes and Scope Of The Special Journal Issuementioning
confidence: 99%